BEING A CAREGIVER OF A CHILD WITH ASTHMA: DISCOURSE ANALYSIS AND STUDY OF ITS MEANINGS - Neila Santini de Souza; Eliane Tatsch Neves; Regina Issuzu Hirooka de Borba (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769210991 Aim: to know the discursive formation and meanings of being a family caregiver of a child with asthma. Method: a descriptive, qualitative approach, which used the creative method - Sensitive developed with families of children with asthma, where we used the Dynamic Creativity and Sensitivity (DCS) Sewing Stories. Data were submitted to discourse analysis in its French strand. Results: it is evident in the discursive formation of the caregiver that meaning is determined by ideological positions, revealing the political and ideological social functioning. Conclusions: it is necessary to review the forms of interaction with the family and act as mediator in shared care with families.